DISTINCT, PARENTAL AND COMMUNAL FACTORS INDUCING JUVENILE DELINQUENCY IN URBAN AREAS: A CASE STUDY OF BORSTAL INSTITUTIONS IN PAKISTAN (Contemporary Journal of Social Science Review, 2025)
This study examines parental and community-related factors contributing to juvenile delinquency in urban Pakistan, focusing on Borstal institutions. Juvenile crime is a major social issue with limited research, requiring urgent prevention and intervention strategies. The research explores how family dynamics, peer associations, and social environments shape delinquent behavior. Findings reveal that lack of parental supervision, family conflicts, and financial instability significantly contribute to delinquency. Many juveniles face domestic violence, neglect, or criminal influences at home, while peer pressure and gang associations further increase their risk. In urban areas, exposure to criminal networks heightens involvement in illegal activities. Rising juvenile offenses necessitate identifying root causes and proposing interventions. Using a qualitative survey and thematic analysis, the study provides insights for policymakers. Recommendations include parental education, community centers, school-police partnerships, enhanced vocational training in Borstal institutions, and strengthening rehabilitation-focused juvenile justice policies to support reintegration.